Proceedings of the 10th Economics &Amp; Finance Conference, Rome 2018
DOI: 10.20472/efc.2018.010.002
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Foreign Direct Investment in Gulf Cooperation Council (Gcc) Region

Abstract: This study aims to find the main determinants of foreign direct investment (FDI) in Gulf Cooperation Council (GCC) Region using a panel data from 1996-2016. The GCC region is facing new economic reforms as a result of low oil prices when oil is the main product of GDP in GCC. In addition, GCC impose tax in 2018 that would affect economy negatively due to lowering in purchase power. Based on lower prices of oil, Saudi Arabia released a plan called Vision 2030. This vision was announced in 26 April 2016 by Crown… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
1
3
0
Order By: Relevance
“…H7: Arab Spring: as expected, over the period of the Arab Spring (2011-2013), the FDI inwards in Saudi Arabia decreased significantly. This result is in line with the finding of Alharthi (2018) who confirmed that in the Arab Spring period, the FDI inwards decline significantly in the GCC countries.…”
Section: Findings Of the Study And Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…H7: Arab Spring: as expected, over the period of the Arab Spring (2011-2013), the FDI inwards in Saudi Arabia decreased significantly. This result is in line with the finding of Alharthi (2018) who confirmed that in the Arab Spring period, the FDI inwards decline significantly in the GCC countries.…”
Section: Findings Of the Study And Discussionsupporting
confidence: 92%
“…FDI inwards and Arab Spring In 2011, the political instability in the Middle East and North Africa (MENA) region was expanded and this political instability called Arab Spring (Arab political revelations). Alharthi (2018) found that Arab Spring has affected FDI inwards for GCC countries. The seventh hypothesis is: H7: Arab Spring impacts FDI inwards in Saudi Arabia significantly…”
Section: Fdi Inwards and Tradementioning
confidence: 99%
“…Other empirical studies have used different econometric techniques to estimate the determinants of FDI inflows on different countries (Alharthi, 2018). A study conducted by Asongu et al (2018) on and MINT (Mexico, Indonesia, Nigeria, and Turkey) countries demonstrated that market size, infrastructure availability, and trade openness play significant roles in attracting FDI.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Secondly, a variety of theoretical models has been used in previous studies. Thirdly, a number of different econometric techniques have been implemented in empirical studies to test and estimate FDI determinants (Alharthi, 2018). On the contrary, the disparity in outcomes does not prevent the requirement for additional investigation of the subject as long as it is apparently represented that the investigation and the obtained findings are not mandatorily generalized to other cases.…”
Section: Introductionmentioning
confidence: 99%